Digital Wisdom : A Reconstruction of Christian Leadership Theology in the Age of Algorithms and Echo Chambers - Andre Shevcenco Mumu (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
The era of technological disruption, driven by the economic logic of "surveillance capitalism," has created a fragmenting digital architecture. The "filter bubble" or "echo chambers" mechanism algorithmically isolates individuals, exacerbated by a psychological condition of being "alone together" wherein individuals actively engage in a "flight from conversation." This convergence of algorithmic and psychological isolation has fueled an "age of outrage" and extreme social polarization. This crisis is fundamentally theological, as it reduces the dignity of the Imago Dei (image of God) to mere exploitable computational data. This research employs a qualitative library study method with a critical-analytical approach to analyze this phenomenon and propose a reconstruction of Christian leadership theology. This article argues that Christian leaders must develop a new theological competency termed "Digital Wisdom." This wisdom is rooted in a holistic theology that resists dualistic fragmentation. This reconstruction is embodied in the leader's role as spiritual (placing the Word of God as authority over algorithms), educational (building digital ethics and combating disinformation), integrity-based (rejecting partisan outrage), and humanistic (reaffirming the primacy of physical encounter and authentic relationship).